2020
DOI: 10.5336/nurses.2019-73129
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Relationship Between Surgical Fear Levels and Postoperative Pain Levels in Patients Undergoing Total Knee Prosthesis Surgery

Abstract: Total diz protezi ameliyatı planlanan hastaların, cerrahi korku düzeyleri ile ameliyat sonrası ağrı düzeyleri arasındaki ilişkinin belirlenmesidir. Gereç ve Yöntemler: Tanımlayıcı özellikte olan araştırmanın uygulaması, Aralık 2018-Mayıs 2019 tarihleri arasında Ankara ilinde bulunan bir vakıf hastanesine total diz protezi ameliyatı olmak için başvuran, örnekleme dâhil olma kriterlerine uyan ve katılmayı kabul eden 74 hasta ile yapılmıştır. Araştırmanın verileri "hasta tanıtıcı bilgileri veri toplama formu", "S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Another study by Çetin and Yılmaz 19 reported that fear of surgery in surgical patients was at a low level. Mete and Işık 20 determined that patients who underwent total knee prosthesis surgery experienced moderate surgical fear. Patients who have undergone cardiac or thoracic surgery can be mobilized earlier and more frequently and become independent in activities of daily living more quickly.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Çetin and Yılmaz 19 reported that fear of surgery in surgical patients was at a low level. Mete and Işık 20 determined that patients who underwent total knee prosthesis surgery experienced moderate surgical fear. Patients who have undergone cardiac or thoracic surgery can be mobilized earlier and more frequently and become independent in activities of daily living more quickly.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the surgical fear levels of patients were found to be below the average level. Likewise, Mete and Avcı Işık (2020) and Garcia et al (2018) determined the fear levels of patients below the average level before total knee arthroplasty and before colorectal cancer surgery, respectively. Kaya and Özlü (2019) and Altun et al (2017) found the fear levels of patients before elective surgical intervention at a medium level.…”
Section: Discussionmentioning
confidence: 99%